The euro and its central bank : getting united after the union - Padoa-Schioppa, Tommaso (Cambridge, Mass. : MIT Press, 2004)
History and analysis of European monetary integration and related economic, financial, monetary, and international political issues: an accesible guide.
Includes bibliographical references (p. 231-242) and index.
oif 21/08/15
Loan
Keywords: Euro; European Central Bank; Monetary policy -- European Union countries